Gramsci at the margins: subjectivity and subalternity in a theory of hegemony - Smith, Kylie (International Gramsci Journal, 2023)
In strictly political terms, the Gramscian concept of subalternity applies to those groups in society who are lacking autonomous political power. In Gramsci’s time these groups were easily identified, and much of the work around the concept of subalternity has centred on groups like peasants and the proletariat. But Gramsci also argued that subalternity existed on a broader scale than this, including people from different religions or cultures, or those existing at the margins of society. This aspect of Gramsci’s work is often overlooked, because many writers are interested in Gramsci’s political theory, which they use to analyse the way in which capitalism, as a structural system, has become hegemonic over time. The focus here is on the history of organised groups and their organised struggle. Hence, the emphasis is largely on white, male-oriented institutions of power. But Gramsci argued that hegemony did not exist merely at this level. Rather, he argued that hegemony comes from below, originating in the thoughts, beliefs and actions of everyday people who may or may not see themselves as part of organised groups. Hence, Gramsci was intensely aware of the way hegemony operated at a personal level. Capitalist hegemony was not, is not, possible, without a complete identification at the level of the self. This paper seeks to expand on some of Gramsci’s thinking in this area, in an attempt to understand the connections between the self and society in a theory of hegemony, where hegemony is considered a process based on leadership, rather than a state built on domination. It is through an analysis of what hegemonic processes exclude (or make subaltern), that we can expand our understanding of how hegemony works, and of how it may be resisted.